2013
DOI: 10.1007/s10499-013-9686-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of safflower oil supplementation in diet on growth performance and body fatty acid composition of turbot (Psetta maxima)

Abstract: The aim of the study was to investigate the effects of the diets that contain safflower oil and fish oil as lipid sources, on growth, feed conversion and body composition in turbot (Psetta maxima). Two iso-nitrogenous and iso-lipidic diets (55 % protein and 14 % lipid) were prepared that include 100 % fish oil (FO group) and 100 % safflower oil (SFO group) for turbots with average weight of 62.21 ± 1.28 g, and fish were fed with these diets for 104 days. At the end of the experiment, the weight gain, specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
(23 reference statements)
0
4
0
1
Order By: Relevance
“…The replacement of 50% dietary fish oil with unrefined peanut oil had no adverse effect on the growth performance of common carp (Yildirim et al 2013). There were no significant effects on weight gain in White sturgeon (Xu et al 1993) and no negative effects on growth of turbot fed diets containing SFO (Bell et al, 1994;Altundag et al 2014). Partial replacement of cod liver oil with either linseed or SFO did not have a negative effect on growth performance in juvenile Eurasian perch (Blanchard et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…The replacement of 50% dietary fish oil with unrefined peanut oil had no adverse effect on the growth performance of common carp (Yildirim et al 2013). There were no significant effects on weight gain in White sturgeon (Xu et al 1993) and no negative effects on growth of turbot fed diets containing SFO (Bell et al, 1994;Altundag et al 2014). Partial replacement of cod liver oil with either linseed or SFO did not have a negative effect on growth performance in juvenile Eurasian perch (Blanchard et al 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Regarding other medical herbs and oils, Sahu et al (2008) reported significant increase in specific growth rate in Labeo rohita fingerlings fed diets contained four levels from turmeric (0.1, 0.5, 1.0 and 5g ). Altundag et al (2014) reported significant differences in specific growth rate in favor of diets contained sun flower oil (0.65%) compared to diets contained fish oil (0.58%) in a study on turbot (Psetta maxima).…”
Section: Specific Growth Ratementioning
confidence: 99%
“…Concomitantly, studies to curtail fish oil consumption in aquaculture with inexpensive and readily available lipid sources that do not compromise fish growth and health have garnered increasing attention (Altundag, Tiril, & Ozdemir, ; Huang et al, ; Peng, Xu, et al, ; Regost, Arzel, Robin, Rosenlund, & Kaushik, ; Turchini, Torstensen, & Ng, ; Zhou et al, ). However, some studies reported that terrestrial lipid sources alter fish feed intake, digestion and metabolism (Huang et al, ), which affect fish growth and flesh quality (Kim et al, ; Zhou et al, ), due to variation in the fatty acid composition between fish oil and terrestrial lipids.…”
Section: Introductionmentioning
confidence: 99%
“…attention (Altundag, Tiril, & Ozdemir, 2014;Huang et al, 2014;Peng, Xu, et al, 2014;Regost, Arzel, Robin, Rosenlund, & Kaushik, 2003;Turchini, Torstensen, & Ng, 2009;Zhou et al, 2015).…”
unclassified